Kemampuan Literasi Matematika Siswa Berdasarkan Gender - Isnaniah Isnaniah; M. Imamuddin; Charles Charles; Syahrul Syahrul; Zulmuqim Zulmuqim (Lattice Journal : Journal of Mathematics Education and Applied, 2021)
Literacy is an ability that must be possessed by every individual (student). Literacy plays an important role for students. One of the literacy that must be mastered by students is mathematical literacy. Regarding mathematical literacy, many previous researchers have conducted research and even recent research related to this literacy ability is associated with gender. This study aims to map and describe students' literacy skills and differentiate students' literacy skills based on gender. This research is a literature study research by referring to eight article documents. The article documents used as sources were taken randomly from the internet. The results of the analysis of this article document are as follows: 1. Research related to literacy and gender is mostly carried out at the high school level than at the junior high school level, 2. The indicators used in assessing students' literacy abilities are indicators modified from indicators used by the Quasar General Rubric , indicators used by PISA and indicators referring to problem solving steps, and 3. male students' mathematical literacy skills are better than female students' mathematical literacy skills. Literasi merupakan kemampuan yang harus dimiliki oleh setiap individu (siswa). Literasi memegang peranan penting bagi siswa. Salah satu literasi yang harus dikuasai oleh siswa adalah literasi matematika. Terkait literasi matematika, sudah banyak peneliti terdahulu melakukan penelitian bahkan penelitian terkini terkait kemampuan literasi ini dikaitkan dengan gender. Penelitian ini bertujuan untuk memetakan dan mendeskripsikan kemampuan literasi siswa dan membedakan kemampuan literasi siswa berdasarkan gender. Penelitian ini adalah penelitian studi literatur dengan merujuk kepada delapan dokumen artikel. Dokumen-dokumen artikel yang digunakan sebagai sumber diambil secara acak dari internet. Hasil dari analisis terhadap dokumen artikel ini adalah sebagai berikut: 1. Penelitian terkait literasi dan gender lebih banyak dilakukan di tingkat SMA daripada tingkat SMP, 2. Indikator yang digunakan dalam menilai kemampuan literasi siswa yaitu indikator yang dimodifikasi dari indikator yang digunakan oleh Quasar General Rubric, indikator yang digunakan PISA dan indikator yang mengacu pada langkah-langkah penyelesaian masalah, dan 3. kemampuan literasi matematika siswa laki-laki lebih baik daripada kemampuan litetarasi matematika siswa perempuan.